Are men more apologetic than women? - Turiman, Syamimi; Leong, Amelia; Hassan, Fauziah (Universiti Putra Malaysia Press, 2013)
Apologies are common utterances. When an individual has violated a social norm, apologetic utterances are offered. This study investigates how apologies are used in relation to gender. A total of 120 ESL learners were asked to respond to a Discourse Completion Test that had 4 apology situations. Their responses were categorised into different speech act strategies. The results suggest that women tend to apologize more than men. Men and women also differ in the order of primary strategies used. There is a difference in the frequencies and the type of apology strategies used when the respondents apologized to their own gender compared to the opposite.